(untitled) (Journal of Shaheed Suhrawardy Medical College, 2024)
Background: General anaesthesia is usually performed for breast surgery but the risks and complications of general anaesthesia outweigh its benefits. For this, segmental thoracic spinal anesthesia might be an alternative to general anesthesia. Objectives: The objective of this study was to evaluate the effectiveness segmental thoracic spinal anaesthesia in breast surgery. Methods: This prospective observational study was conducted at surgery operation theatre in the Shaheed Suhrawardy Medical College and Hospital, Dhaka, Bangladesh from January 2023 to December 2023. Patients of ASA (American Society of Anesthesiologist) class I and II, ageing above 18 years, and BMI < 35 kg/m2 scheduled for breast surgery (modified radical mastectomy for carcinoma breast, lumpectomy for breast lump/gynaecomastia, and wide local excision for phylloids tumor) were included in this study. Segmental thoracic spinal anaesthesia was performed at T5-T6 space with injection 0.5% hyperbaric bupivacaine 1 ml (5mg) and fentanyl 0.5 ml (25 microgram). Perioperative hemodynamic changes, unwanted effects, time of first rescue analgesic, total opioid consumption in first 24 h, patient and surgeon satisfaction score were recorded in a data sheet. Results: Sixty patients were eligible for the study but 55 patients completed the study successfully. Modified radical mastectomy, Lumpectomy and Wide local excision were done in 42 (76%), 8 (15%) and 5 (9%) patients, respectively. The mean age of the patients was 50.78±8.98 years. There were no significant changes in haemodynamic parameters during the intraoperative period. The frequency of adverse effects were minimal. Mean time for 1st dose of analgesic was 5.8±1.8 hours and total opioid consumption was 76.77±15.7 mg in first 24 hours. Both patient (91%) and surgeon (95%) were highly satisfied with this technique. Conclusions: Segmental thoracic spinal anaesthesia provides better satisfaction and fewer complications in patients undergoing breast surgery. This regional anaesthesia technique can be used effectively for breast surgeries. J Shaheed Suhrawardy Med Coll 2022; 14(2): 47-52